Idiopathic generalised epilepsy of late onset: a separate nosological entity?. Issue 11 (27th August 2010) - Reichsoellner, J; Larch, J; Unterberger, I; Dobesberger, J; Kuchukhidze, G; Luef, G; Bauer, G; Trinka, E
Abstract : Aim: Seizure onset in idiopathic generalised epilepsies (IGE) is considered to be rare after the second decade of life. The authors aimed to explore age of seizure onset in patients with IGE and compare 'classical' onset to late onset cases. Methods: Patients with IGE, treated at the outpatient epilepsy clinic (Medical University of Innsbruck, Austria, 1985–2006, n=798) were retrospectively screened. The inclusion criteria were: diagnosis of IGE, more than two follow-up (FU) visits, duration of FU more than 1 year and normal brain imaging. The authors analysed demographic data, age of seizure onset, seizure types, syndromes, neuroimaging and EEG findings, seizure triggers and seizure freedom for 1 and 5 years at last FU. Results: A total of 492 patients (mean age at seizure onset 14.6 years, range 0.1–55, SD 7.9) with IGE were identified: childhood absence epilepsy (n=113, range 1–55, SD 6.5), juvenile absence epilepsy (n=75, range 4–39, SD 5.1), juvenile myoclonic epilepsy (n=112, range 2–39, SD 5.7), and epilepsy with grand mal seizures on awakening (n=192 range 1–52, SD 17.3). Population was stratified into three groups: 28 patients with seizure onset at >30 years, 180 patients between 15 and 30 years and 284 patients <15 years. The distribution of seizure types and epilepsy syndromes differed significantly in a group comparison (p<0.001); seizure outcome and other clinical variables did not differ throughout the groups. Conclusion: Apart from age-related onset of seizure types and syndromes with a loose upper limit of onset age, patients with a late onset did not differ from their younger counterparts. These data do not support the view of IGE of late onset as a separate syndrome.